Intraluminal thrombus of the internal carotid arteries: angiographic demonstration of resolution with anticoagulant therapy alone. - Pelz, D; Buchan, A; Fox, A; Barnett, H; Vinuela, F (1986)
Fourteen patients with angiographically demonstrated thrombus in the cerebral vessels were treated immediately with anticoagulant or antiplatelet medication. Follow-up angiograms, obtained in eight cases, showed resolution of the thrombus in seven. In no patient did the thrombus progress to occlude the vessel completely, and no new distal emboli were identified on the follow-up angiograms. There were no new permanent neurologic events in these 14 patients while they were undergoing medical therapy. Six patients subsequently underwent delayed endarterectomy to treat underlying stenoses. Our experience indicates that the presence of intraluminal thrombus may not be a surgical emergency.